Protective effects of Ganoderma lucidum spores on estradiol benzoate-induced TEC apoptosis and compromised double-positive thymocyte development - Jihong Yang; Jihong Yang; Jihong Yang; Haitao Pan; Mengyao Wang; Anyao Li; Guoliang Zhang; Xiaohui Fan; Xiaohui Fan; Zhenhao Li; Zhenhao Li; Zhenhao Li (Frontiers Media S.A., 2024)
Backgroud: Thymic atrophy marks the onset of immune aging, precipitating developmental anomalies in T cells. Numerous clinical and preclinical investigations have underscored the regulatory role of Ganoderma lucidum spores (GLS) in T cell development. However, the precise mechanisms underlying this regulation remain elusive.Methods: In this study, a mice model of estradiol benzoate (EB)-induced thymic atrophy was constructed, and the improvement effect of GLS on thymic atrophy was evaluated. Then, we employs multi-omics techniques to elucidate how GLS modulates T cell development amidst EB-induced thymic atrophy in mice.Results: GLS effectively mitigates EB-induced thymic damage by attenuating apoptotic thymic epithelial cells (TECs) and enhancing the output of CD4+ T cells into peripheral blood. During thymic T cell development, sporoderm-removed GLS (RGLS) promotes T cell receptor (TCR) α rearrangement by augmenting V-J fragment rearrangement frequency and efficiency. Notably, biased Vα14-Jα18 rearrangement fosters double-positive (DP) to invariant natural killer T (iNKT) cell differentiation, partially contingent on RGLS-mediated restriction of peptide-major histocompatibility complex I (pMHCⅠ)-CD8 interaction and augmented CD1d expression in DP thymocytes, thereby promoting DP to CD4+ iNKT cell development. Furthermore, RGLS amplifies interaction between a DP subpopulation, termed DPsel-7, and plasmacytoid dendritic cells (pDCs), likely facilitating the subsequent development of double-negative iNKT1 cells. Lastly, RGLS suppresses EB-induced upregulation of Abpob and Apoa4, curbing the clearance of CD4+Abpob+ and CD4+Apoa4+ T cells by mTECs, resulting in enhanced CD4+ T cell output.Discussion: These findings indicate that the RGLS effectively mitigates EB-induced TEC apoptosis and compromised double-positive thymocyte development. These insights into RGLS's immunoregulatory role pave the way for its potential as a T-cell regeneration inducer.